Quantitative determination of the antidepressant vortioxetine and its major human metabolite in plasma. (November 2015) - Kall, Morten A; Rohde, Morten; Jørgensen, Martin
Background: Vortioxetine is a novel antidepressant that has been developed in a joint partnership between H. Lundbeck A/S and the Takeda Pharmaceutical Company, Ltd.Results: A number of bioanalytical methods have been developed in order to support the nonclinical and clinical development of the drug. Method performance, long-term stability, urine analysis, unspecific binding and metabolites analysis are presented and discussed.Conclusion: Two different method applications for the quantification of vortioxetine and its major human metabolite in human plasma, an isocratic cation exchange HPLC–MS/MS method utilizing C8-SPE sample extracts and a reversed-phase UPLC–MS/MS method with gradient elution of protein precipitated sample extracts, have been validated according to current regulatory standards and applied in support to a large number of nonclinical as well as clinical studies.